Endothelial dysfunction in middle-aged and older men with low testosterone is associated with elevated circulating endothelin-1 - Babcock, Matthew C; DuBose, Lyndsey E; Hildreth, Kerry L; Stauffer, Brian L; Kohrt, Wendy M; Wenner, Megan M; Moreau, Kerrie L (American journal of physiology. Regulatory, integrative and comparative physiology, 2025)
Low testosterone in middle-aged/older men contributes to accelerated vascular aging, including endothelial dysfunction. However, the mechanisms by which low testosterone affects endothelial dysfunction are not well understood. We sought to determine whether higher endothelin-1 (ET-1) levels are associated with reduced brachial artery flow-mediated dilation (FMD) in middle-aged/older men with low testosterone. Plasma ET-1 was quantified in 60 men categorized as young ( = 20, age = 30 ± 4 yr, testosterone = 510 ± 63 ng/dL), middle-aged/older with normal testosterone ( = 20, age = 59 ± 6 yr, testosterone = 512 ± 115 ng/dL), or middle-aged/older with low testosterone ( = 20, age = 60 ± 8 yr, testosterone = 265 ± 47 ng/dL). Endothelial function was determined via brachial artery FMD. Venous and arterial endothelial cells were harvested via endovascular biopsy in a subset of participants and stained for ET-1 expression. Middle-aged/older men with normal testosterone exhibited lower brachial artery FMD (5.7 ± 2.2%) compared with young men (7.3 ± 1.3%, = 0.020), which was exaggerated in middle-aged/older men with low testosterone (4.0 ± 1.8%, = 0.010 vs. middle-aged/older men with normal testosterone). Plasma ET-1 was not different between young (5.6 ± 0.9 ng/dL) and middle-aged/older men with normal testosterone (6.0 ± 1.4 ng/dL, = 0.681) but was higher in middle-aged/older men with low testosterone (7.7 ± 2.8 ng/dL) compared with both groups ( < 0.001 vs. young men; = 0.013 vs. middle-aged/older men with normal testosterone). There was no difference in venous ( = 0.616) or arterial ( = 0.222) endothelial cell ET-1 expression between groups. There was a significant inverse association between plasma ET-1 and FMD ( =-0.371, = 0.004). These data suggest that the accelerated age-associated reduction in endothelial dysfunction in middle-aged/older men with low testosterone is related to higher circulating ET-1. Middle-aged/older men with low testosterone have reduced vascular endothelial function compared with young and age-matched men with normal testosterone. In this manuscript, we demonstrate that men with low testosterone have higher plasma endothelin-1, which is associated with worse brachial artery flow-mediated dilation. The source of higher plasma endothelin-1 remains unknown; however, higher circulating endothelin-1 appears to be a mechanism contributing to reduced vascular endothelial function in men with low testosterone.